ANALISIS SISTEM WARALABA MCDONALD’S DALAM PERSPEKTIF SYARIAH - Nining Nining; Putri Lestari; Tifany Anis Fitria; Mega Oktaviany (Taksasila Edukasi Insani, 2023)
McDonald's is the world's largest fast-food chain, which was founded in 1955 in California, USA. In 1991, McDonald's came to Indonesia and opened its first restaurant in Sarinah, Thamrin. This paper was triggered by the rapid growth of the McDonald's franchise system in Indonesia, and the issue that will be examined is how the McDonald's franchise system is viewed from a Sharia point of view. In the Sharia context, franchising can be considered as a form of cooperation or extortion. According to Antonio in the concept of syirkah in franchising, syirkah is a cooperation agreement between two or more parties to manage a particular business. Both parties invest capital and agree to share joint risks and share profits. From an Islamic perspective, the McDonald's franchise system can be considered as a legal form of cooperation or musyarakahna in business. The Islamic concept of syirkah or musyarakah refers to the cooperation of two or more people in the management of wealth or business with the aim of obtaining profits according to the initial agreement. This research method uses qualitative methods. The purpose of this type of qualitative descriptive research used in this research is to obtain information about the McDonald's franchise system from a Sharia perspective. In short, the McDonald's franchise system can be considered a legitimate form of cooperation in business from an Islamic perspective. However, it is important to pay attention to financial principles and Islamic values in franchise operations.